"I Think It's Still a Male-Dominated World": Detachment Services Assistants' Perceptions and Experiences of a Gendered Police Organization. (July 2023) - Norman, Mark; Ricciardelli, Rosemary
Police organizations, typically considered masculine paramilitary organizations, are employing increasing numbers of women in non-sworn roles. We investigate the experiences and perceptions of a specific group of non-sworn personnel, Detachment Services Assistants (DSAs) working with the Royal Canadian Mounted Police, unpacking their perceptions of a slowly-changing gendered organizational culture. We analyze how their fluid performances of femininities allow them to navigate a gendered workplace environment that, at times, can marginalize them based on their gender and occupational status. The study makes a novel contribution to the policing literature on gender and the role of non-sworn personnel in policing.